Small sea, big problems: chances and challenges of military security in Baltic region - Michał Piekarski (Scientific Journal of the Military University of Land Forces, 2020)
The article aims to analyze the chances and challenges related to the military security of states surrounding the Baltic Sea. Notably, the problem of the protection of maritime traffic and other sea-related economic activities shall be described. Particular attention shall be given to possible scenarios of “hybrid warfare.” Based on possible threats characteristics, several aspects of changes in organizations and ways of employment of naval forces, border, and coast guard forces and special operations forces.